Highly Sensitive Water Detection Through Reversible Fluorescence Changes in a syn-Bimane Based Boronic Acid Derivative - Pramanik, Apurba; Karmakar, Joy; Grynszpan, Flavio; Levine, Mindy (Frontiers in Chemistry, 2022)
Reported herein is a fluorometric and colorimetric sensor for the presence of trace amounts of water in organic solvents, using syn-bimane based boronate ester 1. This sensor responds to the presence of water with a highly sensitive turn-off fluorescence response, with detection limits as low as 0.018% water (v/v). Moreover, analogously high performance was observed when compound 1 was adsorbed on filter paper, with the paper-based sensor responding both to the presence of liquid water and to humid atmospheres. Reusability of the paper-based sensor up to 11 cycles was demonstrated, albeit with progressive decreases in the performance, and 1H NMR and mass spectrometry analyses were used to explain the observed, hydrolysis-based sensor response.